2015
DOI: 10.1016/j.molmet.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet and obesity compromise fetal hematopoiesis

Abstract: ObjectiveRecent evidence indicates that the adult hematopoietic system is susceptible to diet-induced lineage skewing. It is not known whether the developing hematopoietic system is subject to metabolic programming via in utero high-fat diet (HFD) exposure, an established mechanism of adult disease in several organ systems. We previously reported substantial losses in offspring liver size with prenatal HFD. As the liver is the main hematopoietic organ in the fetus, we asked whether the developmental expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 63 publications
(79 reference statements)
5
48
2
Order By: Relevance
“…Importantly, there are likely several other aspects of fetal exposure to the maternal HFD that may influence fetal lung maturation such as fetal hyperglycemia and/or fetal hyperinsulinemia (factors not specifically assessed here). Maternal obesity secondary to HFD consumption appears to be deleterious to fetal development in many ways, including by constraint of fetal growth and expansion of fetal liver hematopoietic stem and progenitor cells as discussed in a recent study (19). Collectively, the present study suggests that maternal HFD before and during pregnancy induces elevations in maternal glucose and insulin, placental inflammation resulting in placental insufficiency, FGR, and attenuation of normal fetal lung development and maturation.…”
Section: Discussionsupporting
confidence: 61%
“…Importantly, there are likely several other aspects of fetal exposure to the maternal HFD that may influence fetal lung maturation such as fetal hyperglycemia and/or fetal hyperinsulinemia (factors not specifically assessed here). Maternal obesity secondary to HFD consumption appears to be deleterious to fetal development in many ways, including by constraint of fetal growth and expansion of fetal liver hematopoietic stem and progenitor cells as discussed in a recent study (19). Collectively, the present study suggests that maternal HFD before and during pregnancy induces elevations in maternal glucose and insulin, placental inflammation resulting in placental insufficiency, FGR, and attenuation of normal fetal lung development and maturation.…”
Section: Discussionsupporting
confidence: 61%
“…Similar mechanisms may contribute to the impaired fetal hematopoiesis that is observed with maternal obesity (128).…”
Section: What Are the Initiators Of Metainflammation?mentioning
confidence: 92%
“…Using a combination of colony formation assays, flow cytometry, and gene expression experiments, studies showed that maternal HFD restricts physiologic expansion of fetal HSCs, compromises repopulation of precursor cells in fetal liver, and biases cellular differentiation toward the myeloid branch. 105 This bias toward myeloid lineage and dysregulated hematopoiesis was shown to be dependent on TLR4 signaling. 106 Moreover, metabolic rewiring and increased energy demand of stem cells have been recently reported in mesenchymal stem cells isolated from human cord blood samples obtained from babies born to mothers with obesity.…”
Section: Pregravid Obesity and Changes In Offspring Stem Cellsmentioning
confidence: 99%
“…Data from several studies indicate that hematopoietic stem cell (HSC) populations are exquisitely sensitive to an obesogenic environment. Using a combination of colony formation assays, flow cytometry, and gene expression experiments, studies showed that maternal HFD restricts physiologic expansion of fetal HSCs, compromises repopulation of precursor cells in fetal liver, and biases cellular differentiation toward the myeloid branch . This bias toward myeloid lineage and dysregulated hematopoiesis was shown to be dependent on TLR4 signaling .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation